An Intrusion Theory of Privacy. - Panichas, George (Res Publica (13564765), 2014)
This paper offers a general theory of privacy, a theory that takes privacy to consist in being free from certain kinds of intrusions. On this understanding, privacy interests are distinct and distinguishable from those in solitude, anonymity, and property, for example, or from the fact that others possess, with neither consent nor permission, personal information about oneself. Privacy intrusions have both epistemic and psychological components, and can range in value from relatively trivial considerations to those of profound consequence for an individual's dignity, integrity, and autonomy. Thus while the focus of this theory is privacy per se-privacy as being free from certain kinds of intrusions-it has significant implications, discussed briefly, for what properly counts as the content of moral or legal rights to privacy.